From Design to Delivery: The Strategic Role of Product Managers in Deploying AI Solutions for Patient-Centered Healthcare - Gerrit Jacob (International Journal of Scientific Research in Science and Technology, 2025)
In practice, AI adoption could improve patient outcomes and many initiatives fail to move from prototype to practice. The focus of this paper is on the strategic role of product managers in bridgeing between development and patient-centered deployments. Using information from research on AI in medicine, including Bajwa et al. 2021; Chustecki et al. 2024; Wells et al. 2025; and models of AI product development that are examined in Higgins & Madai 2020; Witkowski et al. 2025 and published recent literature on AI in medicine, we synthesize current models and propose a refined framework for developing AI in healthcare. We argue that product managers are able to help cross-functional alignment (engineering, clinical, regulatory) and that AI solutions remain grounded in the user needs and ethical constraints. One key role for stakeholders is stakeholder translation, iterative validation, risk governance, and feedback integration. Case studies and approaches like FAIR-AI, implemented at scale, highlight success factors and barriers to adoption. The result is a conceptual model from design to delivery that addresses patient safety, transparency, and adaptability. This research is also useful to theory and practice by providing a guide to product management in AI healthcare; and suggests recommendations for empirical validation for future studies.
Keywords: AI in Healthcare; Product Management; Clinical Innovation; Patient-Centered Design; Artificial Intelligence Deployment; Health Technology Management; Digital Transformation in Medicine; Healthcare Product Strategy; Ethical AI; Clinical Readiness